THE MEDICALIZATION OF SOCIETY. CONCEPTUAL AN ETHICAL CONTROVERSIES - ȘARGU, Elena (Studia Universitatis Babeş-Bolyai Bioethica, 2018)
In order to support the evolution of medicine and to overcome the existing challenges, the phenomenon of medicalization becomes more and more remarkable in the field of medicine. Being conscious about the importance of forming a mentality on one's own health is the primary desideratum in a society where pathologies have become more and more numerous due to the distortion of the boundaries between health and disease.